Antiviral treatment associated with reduced risk of clinical Alzheimer's disease—A nested case‐control study - Eva‐Stina Hemmingsson; Ellen Hjelmare; Bodil Weidung; Jan Olsson; Maria Josefsson; Rolf Adolfsson; Lars Nyberg; Fredrik Elgh; Hugo Lövheim (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2021)
Abstract Introduction In this nested case‐control study, we investigated if antiviral treatment given prior to onset of Alzheimer's disease (AD) could influence incident AD. Methods From a large population‐based cohort study in northern Sweden, 262 individuals that later developed AD were compared to a non‐AD matched control group with respect to prescriptions of herpes antiviral treatment. All included subjects were herpes simplex virus 1 (HSV1) carriers and the matching criteria were age, sex, apolipoprotein E genotype (ε4 allele carriership), and study sample start year. Results Among those who developed AD, 6 prescriptions of antivirals were found, compared to 20 among matched controls. Adjusted for length of follow‐up, a conditional logistic regression indicated a difference in the risk for AD development between groups (odds ratio for AD with an antiviral prescription 0.287, P = .018). Discussion Antiviral treatment might possibly reduce the risk for later development of HSV1‐associated AD.